Spontaneous subdural haematoma in a patient with a total artificial heart on warfarin. Issue 9 (4th September 2019) - Moledina, Saadiq; Shanmuganathan, Mayooran; Pathak, Suraj; Simon, Andre
Abstract : We present the unusual case of a middle-aged woman who developed a spontaneous subdural haematoma (SSH) while on oral anticoagulation therapy for a total artificial heart (TAH). Headache was followed by paraesthesia and numbness of the left hand. The diagnosis was made from a CT scan. Symptoms resolved with conservative management and careful control of anticoagulation. In this case report, the risk factors and pathophysiology behind this condition are explored. TAHs in their own entity are a rare phenomenon. Coupled with the highly unusual presentation of an SSH in which only a few cases have been documented, we hope to highlight the management of such a difficult case. After navigating this complication, we were able to successfully bridge this patient to a heart transplant 26 days after the SSH.